Graphex 5 : 5th annual juried exhibition of Canadian prints and drawings. - The Art Gallery of Brant, Brantford; Belshaw, Linda (Brantford : Art Gallery of Brant, 1977)
Adams, Rodney ; Anderson, Jack ; Apanasowicz, Jerry ; Beam, Carl ; Belda, Serge ; Besant, Derek ; Biden, Doug ; Bjerksetl, Philip ; Boughner, J. ; Bucholtz-Ross, L. ; Cavanagh, Ted ; Chilton, Vernon ; Cole, Sandra ; Coy, Beverley ; Darling, Lulu ; Davison, Betty ; Deacon, Peter ; Drum, Sydney ; Evermon, Bob ; Ford, Susan ; Forman, Ann ; Frye, Todd ; Gardiner, Leonard ; Geden, Dennis ; Gersovitz, Sarah Valerie ; Gorman, David ; Gouin, Judy ; Haeseker, Alexandra ; Hantiuk, Margaret ; Hawken, George ; Heywood, J.C. ; Holdsworth, Geoffrey ; Hurst, Patrick ; Kemble, Diana ; Klymkiw, Orysia ; Laing, Bill ; Lajoie, Paul ; Lapointe, Frank ; Law, William ; MacNeil, Brad ; Martin, Ian ; May, Margaret ; McKeough, Rita ; Merkur, Sharon ; Merritt, David ; Michael, Michelle ; Monahan, Thomas ; Morin, Doreen ; Morrissey-Clayton, M. ; Morrison, Hugh ; Nicoll, Marion ; Oberheide, Heide ; Osborne, Lyndal ; Osicka, Peter ; Porter, Edward ; Pottruff, Rick ; Quackenbush, Diane ; Reid, Leslie ; Smutylo, allen ; Sopher, Shelley ; Stogre, P.A.Z. ; Struble, Bradley ; Tait, M. ; Tamasauskas, Otis Kazys ; Waugh, Phyllis ; Weber, Kay Murray ; Wright, Don ; Wright, Graham ; Zeigler-Sungur, Barbara
Graphex 5 : 5th annual juried exhibition of Canadian prints and drawings, The Art Gallery of Brant, Brantford, April 20 - May 28, 1977
Engels
boek
Keywords: Canada